Evaluasi Strategi Aliansi Bisnis Gojek dan Tokopedia dari Perspektif Manajemen Strategik - Ega Juangga; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The strategic merger between Gojek and Tokopedia, resulting in the formation of GoTo, marks a significant milestone in Indonesia's digital industry landscape. This study aims to evaluate the business alliance strategy from a strategic management perspective by analyzing operational efficiency, synergy value, regulatory challenges, and its broader impact on the national digital ecosystem. Using a qualitative approach through literature review and secondary data analysis, the findings indicate that the GoTo merger led to cost efficiencies, strengthened service ecosystems, and significant revenue growth. However, internal integration processes and regulatory challenges—such as potential monopolistic practices and data protection—remain critical strategic concerns. The merger not only positions GoTo as a dominant player in Southeast Asia’s digital economy but also serves as a model for digital transformation in Indonesia. These insights are relevant for policymakers, business practitioners, and scholars seeking to understand alliance strategies in the context of the evolving digital economy.